Investigating the Protective Effect of Resveratrol on Hepatotoxicity and Oxidative Stress Caused by 3-monocholoropropan1-2diol in Rats - Farzaneh Motafeghi; Mahsa Deilamian; Shaghayegh shokrzadeh; Mohammad shokrzadeh (Pharmaceutical and Biomedical Research, 2023)
Background and Objectives: 3-monocholoropropan1-2diol (3MCPD) is a chlorohydrin glycerol known as a toxic substance in food processing. This substance can cause toxicity in various organs, such as the kidney, liver, reproductive system, etc. This study investigates the protective effect of resveratrol on hepatotoxicity and oxidative stress caused by 3MCPD in rats. Methods: A total of 30 male adult rats were obtained and kept under standard conditions. Animals were divided into five groups of 6 rats, including the control group (normal saline), 3MCPD group (10 mg/kg), 3MCPD+resveratrol group (25 mg/kg), 3MCPD+resveratrol group (50 mg/kg), and 3MCPD+resveratrol (100 mg/kg) group. Injections were done intraperitoneally for 14 days. Then, 24 h after the last injection, the liver tissue was removed to evaluate oxidative parameters. Results: 3MCDP could increase reactive oxygen species and decrease glutathione levels and mitochondrial activity; however, no significant lipid peroxidation was observed in the group receiving 3MCDP. Also, the simultaneous administration of resveratrol could reduce the level of reactive oxygen species and lipid peroxidation and increase the level of glutathione and mitochondrial activity. Conclusion: 3MCDP can cause toxicity in the liver of rats by inducing oxidative stress. Also, resveratrol, having antioxidant properties, can inhibit this toxicity.